Patterns of Interpersonal Communication Relationships Between Parents and Children in Character Building Students (Case Study at SDI A-Education, Ketawang Village, Jogosatru, Wonoayu District, Sidoarjo Regency) - Davina Feri Fatmala; Didik Hariyanto (Indonesian Journal of Cultural and Community Development, 2022)
This study shows that the pattern of communication between teachers and students in shaping the character of students in grades 1-4 of SDI A-Education, Ketawang Jogosatru Village, Sidoarjo Regency is a pattern of interpersonal communication. This is evidenced by the practice of the elements of interpersonal communication patterns in the communication that exists between teachers and students towards the character formation of students in grades 1-4 of SDI A-Education, Ketawang Jogosatru Village, Sidoarjo Regency. As with quotations, communication patterns are simply divided into two. The first is a positive communication pattern, which is communication that can certainly bring positive outputs such as cooperative attitude, tolerance, sincerity, understanding and cooperation. Second, the negative communication pattern which is communication can certainly bring negative impacts such as hatred, doubt, misunderstanding, doubt, hostility, and revenge (West & Turner, 2013: 25). The pattern of communication is a form of communication process, so that with the existence of various forms of communication, and part of the process of communication will be able to find patterns that are easy and suitable for use in communicating.